3D ordered macroporous SmCoO3 perovskite for highly active and selective hydrogen peroxide detection. (10th January 2018) - He, Juan; Zhou, Wei; Sunarso, Jaka; Xu, Xiaomin; Zhong, Yijun; Shao, Zongping; Chen, Xiangjian; Zhu, Hua
Abstract: We reported the direct electrochemical hydrogen peroxide detection on three-dimensionally ordered macroporous SmCoO3 (3DOM-SmCoO3 ) perovskite oxide electrode synthesized via a poly (methyl methacrylate) (PMMA) colloidal crystal templating route. The low-cost and simple 3DOM-SmCoO3 sensor not only overcome the various disadvantages of enzyme- and noble metal-based sensors but also display a superior sensing performance for H2 O2 detection. More importantly, using 800 nm PMMA microspheres, a hexagonally ordered macroporous crystalline structure can be created, which features large surface area (20.14 m 2  g −1 ) and large, open, interconnected channels for facile reactants and ions diffusions. The resultant 3DOM-SmCoO3 synthesized using 800 nm PMMA microspheres template (3D-SC-800) displayed higher sensitivity (715 and 460 μA mM −1  cm −2 ), lower limit of detection (0.004 μM), larger detection linear range (0.1–10, 000 μM), and higher selectivity in the presence of interfering species (i.e., glucose, ascorbic acid, dopamine, and uric acid), for H2 O2 detection, relative to SmCoO3 (SC) and SmCoO3 synthesized using 200 nm PMMA template (3D-SC-200). Our comprehensive electrochemical characterization attributes the superior H2 O2 electrooxidation performance of 3D-SC-800 to its fast electron transfer kinetics and diffusion rate. What we demonstrated here bolsters the future opportunity to harness ordered macroporous perovskite oxide-based materials for highly active and selective non-enzymatic H2 O2 detection. Graphical abstract: Highlights: 3DOM-SmCoO3 synthesized using 800 nm PMMA microspheres template (3D-SC-800) displayed higher performance in detection of H2 O2 compared with SmCoO3 (SC) and SmCoO3 synthesized using 200 nm PMMA template (3D-SC-200). The excellent electrooxidation activity of 3D-SC-800 due to its larger surface area, faster electron transfer kinetics, and faster diffusion rate. The electrooxidation mechanism occurred via Co 3+ /Co 4+ redox couple and the behavior of such electrooxidation process were discussed using comprehensive electrochemical characterization data.